Uticaj optimalne kontrole krvnog pritiska na progresiju hronicne bubrezne bolesti - Grujičić, Milorad; Popović-Pejičić, Snježana; Marković, Aleksandra (Scripta Medica, 2024)
Background/Aim: Chronic kidney disease (CKD) has seen a rapid increase worldwide in recent decades, now recognised as a global health issue of the 21st century. Optimal, continuous control of hypertension represents a crucial part of treatment capable of slowing the progression of CKD. The aim of this study was to demonstrate that optimal regulation blood pressure control in patients with essential and secondary hypertension, along with CKD, slows the progression of CKD.Methods: The research was conducted at the University Clinical Centre of the Republic of Srpska, Banja Luka, Internal Clinic Nephrology Department. A retrospective-prospective study was blind for patients and lasted for 24 months. It included 97 patients, aged 18 and above, of both genders, hypertensive, in the 3rd or 4th stage of CKD (creatinine clearance of 15-59 mL/min). Assess the outcome of CKD, a "complex (undesirable) clinical outcome" was taken - one of three fundamental clinically undesirable events: double increase in serum creatinine values at the end of 24 months, onset of terminal renal insufficiency, or patient death.Patients were classified into three groups: I group - 30 patients with essential hypertension and CKD with optimally regulated blood pressure; II group - 32 patients with secondary hypertension and CKD with optimally regulated blood pressure; III control group - 35 patients with hypertension of various causes and CKD who did not achieve target blood pressure values. Blood pressure control was measured from month 0 to month 24 - once a month. Laboratory tests were taken every 3 months (red blood cells, haemoglobin, glycaemia, cholesterol, urea, creatinine, uric acid, sodium, potassium in serum and urine). Results: There was a highly statistically significant difference in glomerular filtration rate in the first group compared to the third group and in the second group compared to the third group. No statistically significant difference in glomerular filtration rate between the first and second groups was observed, where good blood pressure regulation was achieved.Conclusion: Optimal blood pressure control in the examined groups, regardless of the cause of CKD, was responsible for slowing the progression of CKD compared to the group with unregulated blood pressure.